PERAN SERTIFIKASI DOSEN, KOMPETENSI SDM DAN BUDAYA KERJA DALAM MENINGKATKAN KINERJA DOSEN UNIVERSITAS KATOLIK INDONESIA SANTU PAULUS RUTENG - Valentius Gara; Chamariyah Chamariyah; Subijanto Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This research was conducted at the Santu Paulus Ruteng Catholic University of Indonesia with a sample size. The research sample was 40 employees. The objectives of this study are 1) To describe the certification of lecturers, human resource competencies, work culture and employee performance at the Catholic University of Indonesia, Santu Paul Ruteng. 2) To test and analyze whether lecturer certification, HR competence and work culture have a simultaneous and significant effect on the performance of the employees of the Catholic University of Indonesia, Santu Paul Ruteng. 3) To test and analyze whether lecturer certification, human resource competence and work culture have a partial and significant effect on the performance of the employees of the Catholic University of Indonesia Santu Paul Ruteng. 4.) To test and analyze which variables between lecturer certification, human resource competence and work culture have a dominant and significant effect on the performance of the employees of the Catholic University of Indonesia Santu Paul Ruteng. Data analysis using SPSS, this type of research is explanatory research using quantitative research approaches. The results showed that: 1). Simultaneously, certification, HR competence and work culture were responded very well by respondents so that it had a significant effect on the performance of lecturers at the Catholic University of Indonesia, Santu Paul Ruteng, proved to be true and the hypothesis was accepted. 2). Partially, Certification, HR competence and Work Culture are responded to very meaningfully / very well by employees so that it has a significant influence on the performance of lecturers at the Catholic University of Indonesia santu paulus ruteng, proven its truth and accepted hypothesis. 3). t test can be seen that the t value on the independent variable the influence of Work Culture is 0.246 with a significant level of 0.03 or less than 0.05, thus it can be concluded that the Work Culture variable, has a positive and significant effect on the lecturer performance variable, at the University. Indonesian Catholic Santu Paul Ruteng.